Gallium-67 radiotoxicity in human U937 lymphoma cells. - Jonkhoff, A. R. (Nature Publishing Group, 1993)
Promising clinical results have been obtained with radiolabeled antibodies in lymphoma patients. The higher uptake by lymphomas of 67Gallium (67Ga) compared with monoclonal antibodies makes selective radiotherapy by the widely available 67Ga appealing. However, the gamma radiation of 67Ga used in scintigraphy is considered to be almost non-toxic to lymphoma cells. However, in addition to photon radiation 67Ga emits low energy Auger electrons and 80-90 keV conversion electrons which could be cytotoxic. The objective of the present study was the assessment of radiotoxicity of 67Ga on a lymphoid cell line: U937. Proliferation (MTT-assay) and clonogenic capacity (CFU-assay) were measured after 3 and 6 days incubation with 10, 20 and 40 microCi ml-1 67Ga. Growth inhibition was 36% after 3 days incubation and 63% after 6 days incubation with 40 microCi 67Ga ml-1. Clonogenic capacity was reduced by 51% after 3 days and 72% after 6 days incubation with 40 microCi ml-1 67Ga. A survival curve showed an initial shoulder and became steeper beyond 200-250 pCi cell-1 (low linear energy transfer type). Iso-effect doses of 67Ga and 90Yttrium (90Y) were determined. The iso-effect dose of 40 microCi 67Ga ml-1 (cumulative dose of conversion electrons 306 cGy) was 2.5 microCi 90Y ml-1 (cumulative dose 494 cGy) and the iso-effect dose of 80 microCi 67Ga ml-1 was 5.0 microCi 90Y/ml. The main cytotoxic effect of 67Ga seems to be induced by the 80 keV conversion electrons. We conclude that the conversion electrons of 67Ga have a cytotoxic effect on U937 cells and that in our experiments a 16-fold higher microCi-dose of 67Ga than of 90Y was needed for the same cytotoxic effect. We believe that 67Ga holds promise for therapeutic use.